The Embodied Gaze: Exploring Applications for Mobile Eye Tracking in the Art Museum. Issue 1 (2nd January 2020) - Garbutt, Michael; East, Scott; Spehar, Branka; Estrada-Gonzalez, Vicente; Carson-Ewart, Brooke; Touma, Josephine
Abstract: Recent advances in Mobile Eye Tracking (MET) technology facilitate the investigation of visitors' embodied visual behaviors as they move through exhibition spaces. Our MET-based pilot study of visitor behaviors in an art museum demonstrates the value of MET for identifying 'hotspots' of attention. The study also confirms the occurrence of the movement patterns identified by Eghbal-Azar in non-art museums and demonstrates how two patterns—'the Long Gaze' and 'Reading'—can be usefully described in more detail. To illustrate this, we report on one visitor's experience with a single painting, noting the complex embodied visual behaviors associated with gazing and reading. Our findings allow us to reflect on the potential benefits of eye tracking not only for mapping visitor engagement but also for promoting it. In contrast to art museum installations that use static eye tracking as a form of visitor engagement, we argue that MET applications enable visitors to observe, reflect on, and potentially modify, personal viewing practices.